Rational design and synthesis of novel diphenyl ether derivatives as antitubercular agents - Kar SS; Bhat G V; Rao PP; Shenoy VP; Bairy I; Shenoy GG (Dove Medical Press, 2016)
Sidhartha S Kar,1 Varadaraj Bhat G,1 Praveen PN Rao,2 Vishnu P Shenoy,3 Indira Bairy,4 G Gautham Shenoy1 1Department of Pharmaceutical Chemistry, Manipal College of Pharmaceutical Sciences, Manipal University, Manipal, India; 2School of Pharmacy, Health Sciences Campus, University of Waterloo, Waterloo, ON, Canada; 3Department of Microbiology, Kasturba Medical College, Manipal, 4Melaka-Manipal Medical College, Manipal University, Manipal, India Abstract: A series of triclosan mimic diphenyl ether derivatives have been synthesized and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Rv. The binding mode of the compounds at the active site of enoyl-acyl carrier protein reductase of M. tuberculosis has been explored. Among them, compound 10b was found to possess antitubercular activity (minimum inhibitory concentration =12.5 µg/mL) comparable to triclosan. All the synthesized compounds exhibited low levels of cytotoxicity against Vero and HepG2 cell lines, and three compounds 10a, 10b, and 10c had a selectivity index more than 10. Compound 10b was also evaluated for log P, pKa, human liver microsomal stability, and % protein binding, in order to probe its druglikeness. Based on the antitubercular activity and druglikeness profile, it may be concluded that compound 10b could be a lead for future development of antitubercular drugs. Keywords: dihenyl ether, tuberculosis, cytotoxicity, druglikeness